Lesson Learned in Understanding Nature’s Laws in Water Induced Disaster Management: Some Examples - Sthapit, Keshar M (The Initiation, 2010)
Every year, there is unfortunate news about the property damage and loss of lives by the water induced disaster. Water induced disasters are the complex natural phenomena as an outcome of the rain and landform guided by the nature's laws. This paper describes some of the nature's laws essential to respect to live in harmony with nature. This includes consideration of angle of repose while using land, natural drainage to be respected during construction, hazard risk zoning to live in flood and landslide affected areas, fault line zone to be avoided for habitation, and toe of a slope is not to be disturbed to reduce slope failure. Water induced disasters such as erosion and flood are the nature's adaptation strategies to the changes in hydrological, physiographical and management or conservation status of the land caused by nature or human activities. Therefore, it is important to understand that these laws need to be understood and respected to live in harmony with nature so that effects and impacts of water induced disaster will be reduced. DOI: 10.3126/init.v3i0.2428 The Initiation Vol.3 2009 57-65